Escasez del marketing y la publicidad de las tiendas “TUTI” de la ciudad de Babahoyo periodo 2021-2022. - Sotomayor Vera, Diana Lourdes (2023)
Marketing and advertising are activities carried out within a company that consist of exercising the necessary techniques to encourage sales of a product or to publicize a new one and stand out in the market above the competition. The objective of this case study is to investigate the potential long-term impacts on the commercial management of TuTi Stores in terms of the design and implementation of marketing techniques or advertising strategies, which are essential to obtain a better market position in the city of Babahoyo. The methodology used was a descriptive research, accompanied by a survey as a tool; therefore, a qualitative and quantitative method was used, also considering the deductive and inductive methods. The results showed that the TuTi Stores in the city of Babahoyo use the hard discount business model, therefore, the company has not allocated the necessary resources for the creation of a strategic marketing and advertising plan to attract the consumer's attention. In conclusion, it is argued that the lack of a marketing plan and advertising strategies by Tiendas TuTi could affect the company in the long term due to the extensive competition in the market dedicated to the sale of household consumer goods, which could cause Tiendas TuTi to lose recognition or market share.